2016
DOI: 10.1515/macvetrev-2015-0061
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Human Equivalent Dose Formula: A Canonical Case Study of Abrus Precatorius Aqueous Leaf Extract in Monogastric Animals

Abstract: There is abundant literature on the toxicity of A. precatorius seeds. However there is a need to define the toxicity limit of the Abrus precatorius leaf in monogastric animals. Human Equivalent Dose (HED) which is equal to animal dose multiplied by animal km (metabolism constant) divided by human km was used to project the LD 50 of fifteen monogastric animals , where human km factor is body weight (kg) divided by body surface area (m 2 ). Human Equivalent No-observable Adverse Effect Doses were determined by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
12
1
1
Order By: Relevance
“…Ibiam et al (2014) determined median lethal concentration (LC 50 =3.259-6.06 mg/L) of Psychotria microphylla in Clarias gariepinus. Saganuwan & Onyeyili (2016) extrapolated LD 50 of mice to rat, hamster, guinea-pig, rabbit, monkey, cat, dog, baboon, children and adult humans using human equivalent dose formula in recognition with principles of reducing, refining and replacing (3R). The preferred rodent species for toxicity studies is the rat, although other rodent species may be used.…”
Section: Advantages Of Toxicity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ibiam et al (2014) determined median lethal concentration (LC 50 =3.259-6.06 mg/L) of Psychotria microphylla in Clarias gariepinus. Saganuwan & Onyeyili (2016) extrapolated LD 50 of mice to rat, hamster, guinea-pig, rabbit, monkey, cat, dog, baboon, children and adult humans using human equivalent dose formula in recognition with principles of reducing, refining and replacing (3R). The preferred rodent species for toxicity studies is the rat, although other rodent species may be used.…”
Section: Advantages Of Toxicity Studiesmentioning
confidence: 99%
“…Median lethal dose is the amount of test agent that can causes death in 50% of test animals. There are different methods used to estimate median lethal dose (Karber, 1931;Reed & Muench, 1938;Miller & Tainter, 1944;Litchfield & Wilcoxon, 1949;Lorke, 1983;ASTM, 1987;Dixon, 1991;Saganuwan, 2011;Saganuwan et al, 2011;Saganuwan & Onyeyili, 2016). Earlier methods adopted for the estimation of median lethal dose used many animals (40-100), but for up-and-down procedure, 4-15 animals can be used (OECD, 1987;2000a,b;2001a,b,c;Stitzel, 2000;UNECE, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Hence the prolong administration of the seeds to animals may cause anemia. Saganuwan and Onyeyili (2016) and Adedapo et al (2007) had earlier reported that Abrus precatorius extract could cause haemolysis. The plant's active principle is abrin, a toxalbumin (phytoprotein), which is antigenic and may be responsible for the observed toxic effects (Saganuwan and Ogalue, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Although, vaccine induced immunosuppression had been reported in humans (Omage et al, 2015), polyvalent canine vaccines cause significant lymphopenia to mitogen about 3-11 days after vaccination. By day 14 post vaccination, the lymphocytopenia changes lymphocytosis (Saganuwan and Onyeyili, 2016) which is beneficial during immune response.…”
Section: Discussionmentioning
confidence: 99%
“…A. australis garzonii venom (100 μg/kg) was neutralized by 4 mg/kg of antivenom injected intravenously . Antivenoms against a number of scorpion venoms have been reported, but the potency of antivenom in relation to the potency of scorpion venom and both LD 50 and ED 50 should be determined paradoxically and canonically . The LD 50 s of intravenous venom from Vipera berus berus (0.4 μg/kg; symptoms included head‐drop, floppy neck, flaccid paralysis of limb, respiratory paralysis, and death), Laticauda colubrine (0.05‐0.13 μg/g), Sri Lankan Bungarus caeruleus (0.07 μg/g), Naja sputatrix and A. australis (0.5 ng) show that the scorpion venoms are highly toxic.…”
Section: Discussionmentioning
confidence: 99%